PEMBERDAYAAN PENGANGGURAN USIA PRODUKTIF MELALUI PELATIHAN VOCATIONAL ENTREPRENEUR SKILLS MENUJU BANTEN BERKARYA DI ERA DIGITAL [EMPOWERMENT OF PRODUCTIVE YOUTH THROUGH TRAINING THE SKILLS VOCATIONAL ENTREPRENEUR TOWARDS BANTEN CREATIVE IN THE DIGITAL ERA] - Anggoro Suryo Pramudyo; Suhendar Suhendar; Enok Nurhayati; Ina Indriana; Benny Irawan (Universitas Pelita Harapan, 2019)
Recorded more than 7536 people of productive age unemployment spread in cities in Banten province. 4473 of them are in four cities, namely the City of Serang, Rangkasbitung, Cilegon, and Pandeglang [1]. They are stranded on the streets and wandering around. The Banten government does not yet have a special program that is progressive, comprehensive, and sustainable to overcome unemployment and Drop Out Youth. In connection with that, the University of Sultan Ageng Tirtayasa Banten offers cooperation programs in the form of Working with Community. The objectives of this program are: 1) to empower productive age unemployed, 2) to provide start-up entrepreneurship skills for the development and promotion of Banten local products, 3) to improve the social status of the unemployment in order to achieve the program of “a less children on the street” heading of Creative and Cultured Banten Communities, 4) to establish an integrative and comprehensive sustainable programs to overcome the problems of unemployed social groups. The method of social transformation is carried out through training in vocational entrepreneur skills. Activities begin with counseling, training, and mentoring. The application of start-up entrepreneurship technology is provided for the promotion of Banten local products. As many as 30 unemployed are divided into three training groups. The types of training provided are: screen printing skills, entrepreneurship, and the use of mobile phones for online business. Three types of training are given for the three groups. The final product in the form of shirt printing is sold off line at tourist attractions of Gunung Pinang and also through the media on line Bukalapak and Tokopedia. This empowerment activity has been able to give change of life of the parties. The unemployed become more confident because they can use mobile phones for entrepreneurship gradually. The community began to seek ideas to develop and promote local Banten products.Bahasa Indonesia Abstrak: Tercatat lebih dari 7536 jiwa pengangguran usia produktif tersebar di kota-kota dalam provinsi Banten. 4473 jiwa diantaranya berada di empat kota, yaitu Kota Serang, Rangkasbitung, Cilegon, dan Pandeglang [1]. Mereka terlantar di jalanan dan berkeliaran.Pemerintahan Banten belum memiliki program khusus yang progresif, komprehensif, dan berkesinambungan untuk mengatasi pengangguran dan Pemuda Putus Sekolah.Sehubungan dengan itu, timUniversitas Sultan Ageng Tirtayasa Banten menawarkan program kerjasama dalam bentuk pengabdian working with community. Tujuan program ini adalah: 1) memberdayakan pengangguran usia produktif, 2) memberikan keterampilan (life skills)start-up enterpreneur untuk pengembangan dan promosi produk lokal Banten , 3) meningkatkan status sosial pengangguran guna mewujudkan program less children on the street menuju masyarakat Banten berkarya dan berbudaya, 4) membuat program integratif dan komprehensif berkelanjutan untuk mengatasi problematika kelompok sosial pengangguran. Metode transformasi sosial dilaksanakan melalui pelatihan vocational entrepreneur skills. Kegiatan dimulai dengan penyuluhan, pelatihan, dan pendampingan. Penerapan teknologi sart-up enterpreneur diberikan untuk promosi produk lokal Banten. Sebanyak 30 pengangguran dibagi menjadi tiga kelompok pelatihan. Jenis pelatihan yang diberikan adalah keterampilan sablon, kewirausahaan, dan pemanfaatan hand phone untuk bisnis on line. Ketiga jenis pelatihan diberikan secara bergantian antar-satu kelompok dengan kelompok lainnya. Produk akhir berupa sablon kaos dijual secara off line di tempat wisata Gunung Pinang dan melalui media on line bukalapak dan tokopedia. Pemberdayaan yang dilaksanakan sedikit banyaknya telah dapat memberi perubahan. Para pengangguran menjadi lebih percaya diri karena dapat memanfaatkan hand phone untuk berwirausahan secara bertahap. Masyarakat mulai keratif mencari ide untuk mengembangkan dan mempromosikan produk lokal Banten.